New Mixed Skyhook and Displacement–Velocity Control for Improving the Effectiveness of Vibration Isolation in the Lateral Suspension System of a Railway Vehicle - Yaojung Shiao; Tan-Linh Huynh (Applied Sciences)
Demands for increasing the velocity and load carrying capacity of railway vehicles are a challenge to the passive suspension systems used for isolating the lateral vibrations of the carbody of a railway vehicle, especially under a wide range of vibration frequencies. Semiactive suspension systems, especially systems with a magnetorheological damper (MRD), have been investigated as promising alternatives. Many control algorithms have been developed for fine-tuning the damping force generated by MRDs, but they have been ineffective in isolating carbody vibrations at or around the resonance frequencies of the carbody and bogie. This study aims to develop a mixed control algorithm for a new skyhook (SH) control and a new displacement–velocity (DV) control to improve the effectiveness of vibration isolation in resonance frequency regions while producing high performance across the remaining frequencies. The damping coefficient of the new SH controller depends on the vibration velocity of the components of the suspension system and the skyhook damping variable, whereas that of the new DV controller depends on the velocity and displacement of the components of the suspension system and the stiffness variable. The values of the skyhook damping variable and stiffness variable were identified from the vibration velocity of the carbody using the trial and error method. The results of a numerical simulation problem indicated that the proposed control method worked effectively at low frequencies, similar to the conventional SH–DV controller, whereas it significantly improved ride comfort at high frequencies; at the resonance frequency of the bogie (14.6 Hz), in particular, it reduced the vibration velocity and acceleration of the carbody by 50.85% and 45.39%, respectively, compared with the conventional mixed SH–DV controller. The simplicity and high performance of the new mixed SH–DV control algorithm makes it a promising tool to be applied to the semiactive suspension of railway vehicles in real-world applications.